Strategi Pemasaran Berdasarkan Analisis SWOT Pada UMKM Coffeshop di Bukittinggi - Gina Amilussholihati; Mutiara Hendri; Afiful Adrian; Emilya Dwinata Putri (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The coffee shop business is one of the most promising businesses because coffee shops currently attract young people who want to enjoy a different experience. However, it cannot be denied that the coffee shop business also has weaknesses and threats. This study employs the application of SWOT analysis on coffee and eatery businesses located in the city of Bukittinggi to identify the strengths, weaknesses, opportunities, and threats of coffee shop businesses. This study adopts a descriptive qualitative approach, where there is no population or sample. The study utilizes informed consent to obtain the necessary information.